The Conflicts of Ultilization of Forest Area in Bukit Basa Limited Production Forest, Rejang Lebong District, Bengkulu Province - Gunggung Senoaji (School of Postgraduate Studies, Diponegoro Univer, 2019)
Bukit Basa Limited Production Forest covers 125 hectares, located in Rejang Lebong District, Bengkulu Province, Indonesia. The main function of limited production forest is to yield forest products, timber and non timber. In Bukit Basa Limited Production Forest, there has been a change of land use from forest land to a crop land. There has been conflict in this forest area. The objective of this study was to describe the characteristics of communities cutivating forest land and to suggest conflict resolution of this forest area. The data were collected by field observation, and interview. The accidental sampling technique was used to select 42 respondents. Legal approaches were used to find solutions to the tenurial conflict. The results showed that land use of Bukit Basa Limited Production Forest, in 2017 was entirely crop land. All of this forest areas have been illegaly occupied by people. The average land area of occupied by a household was 1.24 ha. The people acquired their land by buying (4.76%), renting (21.43%), clearing the forest (42.86%), and inheriting (30.95%). The dependence of this community on the forest area was quite high. Only 38.10% of them had agricultural land outside the forest area; 61.9% depended on the land in the forest area. The contribution of farmers' incomes from agricultural business in forest land was 77.22% of their total income. The legalization of the use of limited production forests as crop lands must be enforced through policy schemes of community-based forest management, such as community forests, village forests, community plantations forest, or partnerships.